Las Tierras Improductivas deben trabajarse comunmente con el Estado para Generar Inversiones Estatales sin Perjudicar al Propietario - Narváez Romero, Saida Caterine (2017)
Currently the Agricultural Development has been part of the socio-economic and political structure of the state, especially is the means of production that allows workers to develop economically. Therefore, the importance and significance of socio-legal problem entitled. "Unproductive land should it worked OFTEN WITH STATE TO GENERATE INVESTMENT STATE WITHOUT PREJUDICE TO THE OWNER" is based on the need for the state to invest preferentially and compulsory in the agricultural sector especially unproductive private land through ownership mixed guaranteed in our Constitution and thus ensure that the property fulfills its social function which would be agricultural production or other nature, as well as owners of these lands would benefit from supporting their property to achieve agricultural development set without harming the two sides and ensure food sovereignty of the population. When performing conceptual, doctrinal and legal study of the problem I have come to realize that farming in our country is very important, but unfortunately in recent years he has left. Farmers to not have the resources necessary to produce their ownership have been forced to abandon agriculture and engage in other work of survival even migrate out of their hometown in search of better days for himself and his family. On the other hand within the law are rights that we possess all persons, without distinction. The Constitution of the Republic of Ecuador in Article 319 says "various forms of organization of production in the economy, including community, cooperatives, public or private business, associative, family, domestic, autonomous and mixed are recognized". The Constitution of the Republic of Ecuador in Article 321 of the states "The State recognizes and guarantees the right to property in their public, private, community, state, associative, cooperative, mixed forms, and should fulfill its social and environmental function" . Therefore the Constitution of the Republic of Ecuador guarantees various forms of organization that all people can use to engage and work together and get benefits for all who work on their properties. Has issued the Agrarian Development Law which aims and purpose is to promote the protection and development of the agricultural sector and provide the entire population of healthy food, there is talk of a number of agricultural policies are undoubtedly important, but they are not executed by the relevant bodies likewise within them is not taken into account the mixed ownership being the state who should be involved in the production and work together with the owners of unproductive land and fulfill what manifests our Constitution guarantee food sovereignty. Consequently this thesis has been found that is a social problem that requires a legal solution, based on field research conducted through surveys and interviews obtaining important criteria for both legal professionals as well as farmers I helped the positive verification of the objectives. Finally it was established that the joint property is not established in the law hindering equality in productive development. Then make conclusions and proposed recommendations that should be met. That is why I allow myself a proposal for the solution based on the reality in which we live, because there is abandonment by the state to agricultural activity and lack of enforcement of laws in our country.